Examination of the environmental consequences of trade regimes in Latin America (2009)
Since the 1990s, Latin America has experienced an expansion of trade and investment regimes that suggest important challenges for environmental management. This document argues that, in order to favour export oriented sectors and attract foreign investment, these trade regimes may: i) Influence environmental management to reflect the needs of the trade community; ii) Superimpose investment rights and protection measures upon public environmental concerns and national environmental laws; iii) Erode the capacity of governments and the willingness of decision-makers to approach key environmental problems that result from trade and investment activities. The representative cases of NAFTA and Mercosur are analysed.